Intention to khat chewing among youths in Raya-Azebo district, southern zone of Tigray, Ethiopia: application of the theory of planned behavior - Atsbaha, Abadi Hailay; Mekonnen, Adugnaw Berhane; Ketema, Bezawit; Gebrehiwot, Tigist Haile; Gebru, Hirut Teame; Alemseged, Embay Amare; Angaw, Yonas; Gebremedhin, Haftay; Gebremeskel, Fre; Hidru, Hagos Degefa; Gufue, Zenawi Hagos (Frontiers in Public Health, 2025)
BackgroundKhat chewing has become a global phenomenon, resulting in significant physical and mental health issues as well as socioeconomic crises. However, evidence is scarce on Ethiopian youths’ behavioral intentions toward khat chewing, particularly in the Raya-Azebo district of the southern zone of the Tigray region. As a result, this study aimed to assess the intention to chew among youths in Raya-Azebo district, Southern Tigray, Ethiopia.MethodsA community-based cross-sectional survey was conducted among 627 youths in northern Ethiopia’s Raya-Azebo district. Data were collected using a structured, interviewer-administered questionnaire. A multivariable linear regression model was used to predict the contribution of independent variables and identify variables strongly associated with chewing among youths.ResultsA considerable proportion, 192 (30.62%) of youths, had the intention to chew khat in the next 6 months. The component of the theory of planned behavior independently explained the variance in intention to chew by 83%. The strongest predictors of intention to chew were attitude (β = 0.35, p < 0.001), subjective norm (β = 0.297, p < 0.001), and perceived behavioral control (β = 0.15, p = 0.01).ConclusionBehavioral intention toward khat chewing was a function of attitude, subjective norm, and perceived behavioral control toward khat chewing. Strategies to empower youths to change a positive attitude toward khat chewing, programs targeted at resisting social pressures, and increasing self-efficacy to combat chewing are needed.